2020
DOI: 10.1038/s41467-020-16026-w
|View full text |Cite|
|
Sign up to set email alerts
|

Adipocyte Piezo1 mediates obesogenic adipogenesis through the FGF1/FGFR1 signaling pathway in mice

Abstract: White adipose tissue (WAT) expansion in obesity occurs through enlargement of preexisting adipocytes (hypertrophy) and through formation of new adipocytes (adipogenesis). Adipogenesis results in WAT hyperplasia, smaller adipocytes and a metabolically more favourable form of obesity. How obesogenic WAT hyperplasia is induced remains, however, poorly understood. Here, we show that the mechanosensitive cationic channel Piezo1 mediates diet-induced adipogenesis. Mice lacking Piezo1 in mature adipocytes demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 60 publications
2
83
0
Order By: Relevance
“…The positive role in early adipogenesis has been described mainly in 3T3-L1 cells also for FGF2 and for FGF1 [ 26 ]. Moreover, recent studies in in vivo and ex vivo murine models indicated that FGF1 is also released by mature adipocytes to induce adipocyte precursor differentiation as a central feedback mechanism by which mature adipocytes control adipogenesis during the development of obesity [ 64 ].…”
Section: Regulation Of Adipocyte Differentiationmentioning
confidence: 99%
“…The positive role in early adipogenesis has been described mainly in 3T3-L1 cells also for FGF2 and for FGF1 [ 26 ]. Moreover, recent studies in in vivo and ex vivo murine models indicated that FGF1 is also released by mature adipocytes to induce adipocyte precursor differentiation as a central feedback mechanism by which mature adipocytes control adipogenesis during the development of obesity [ 64 ].…”
Section: Regulation Of Adipocyte Differentiationmentioning
confidence: 99%
“…As part of their normal function, hypertrophic adipocytes that may have reached their capacity for nutrient storage communicate signals to adipocyte progenitors to expand and differentiate, offering more sites for lipid deposition. 25,94 Two such signals, FGF1 and FGF2, classically activate FGF receptors (FGFRs). Recently, FGF1 was found to be produced by mature hypertrophic adipocytes and released through activation of the mechano-sensing ion channel Piezo1.…”
Section: Cytokines and Growth Factorsmentioning
confidence: 99%
“…Membrane tension was determined as previously described 58,59 . Olympus IX81 microscope (see above).…”
Section: Determination Of Cell Membrane Tensionmentioning
confidence: 99%